Resiliência e suporte social em adolescentes gestantes - Teixeira, Rayssa Matos (2019)
As with resilience, social support presents factors external to the individual as a form of support in the face of adversity, which influences well-being. Social support can be defined as the existence of people who can be trusted, loving, who care about and value the individual. We seek to understand from the knowledge of resilience and social support how children, adolescents and adults are able to overcome negative events and follow positively, despite adverse conditions. Reflecting the practice of unprotected and early sex, during this period, we have sexually transmitted infections, human immunodeficiency virus and acquired immunodeficiency syndrome, as well as unwanted and / or unplanned pregnancies. In addition to the reasons mentioned, the situations of poverty, low education and few job opportunities favor the occurrence of two situations: sexually transmitted infections, human immunodeficiency virus and acquired immunodeficiency syndrome, and teenage pregnancy. The objective is to analyze resilience and social support in pregnant adolescents, infected or not by a sexually transmitted infection, the human immunodeficiency virus or acquired immunodeficiency syndrome. This study is analytical, descriptive, cross-sectional, quantitative. The study was conducted from September 2018 to April 2019. Data were collected from 3 tertiary hospitals that had prenatal outpatient maternity hospitals for pregnant adolescents. The study population consisted of 85 pregnant adolescents, between 12 and 19 years of age, pregnant women, with or without sexually transmitted infections, human immunodeficiency virus and acquired immunodeficiency syndrome. Sample participants were reached for convenience. The collection was carried out with visits to the institutions on the days when there were visits to the adolescent prenatal clinics, and a questionnaire and two self-applicable scales (resilience and Brazilian version of the social support scale) were used. The average of adolescents per day was 3. Each visit to the institutions was carried out two steps. This study was guided by the ethical principles of Resolution 466 of 12 December 2012, with the opinions, Hospital 1: 3,159,417; Hospital 2: 3,325,372; and Hospital 3: 3,197,972. From the application of both scales we obtained as results that 87.1% are resilient and have social support. In addition to internal factors, there is social support that helps in coping with adversity and maintaining resilience. Adolescents who use recurring coping strategies to solve problems and seek social support have higher levels of psychological well-being. Abortion was relevant, showing that when there is support friends, others and teachers, the option of pregnant women to do so can be avoided and changed. It is concluded that despite the inherent changes of adolescence and pregnancy, these adolescents have protective factors that allow them to remain resilient. The factors are the individual and the inherent social support, first others, teachers, family and friends. These factors can be worked on to emphasize resilience, thus softening the difficulties faced in adolescence and pregnancy. The family has support, as long as it is positive and without prejudice.